Desenvolvimento experimental de um equipamento para o tratamento de efluentes de lavagem de carros por eletrólise - Schenkel, Raul (2022)
The waste of water resources and the increase in water consumption in urban systems have generated water scarcity problems. The vehicle washing process is one of the water consumers and generates a considerable volume of potentially polluting effluents, being released directly or with inadequate treatments to the sewage and/or rainwater network. The electrolysis process is a technically viable treatment with the possibility of reusing the effluent, reducing the environmental impact from a compact, low-cost and easy-to-operate equipment. This research aimed at the experimental development of an equipment for the treatment of effluents from a vehicle washing station by electrolysis of a vehicle washing station capable of reducing the environmental impact of this activity through the treatment and reuse of the effluent. To design the project, the product development methodology proposed by PAHL (2005) was used. The designed equipment was composed of an electrolytic chamber composed of two hives with aluminum electrodes with the capacity to treat 500 l/h, the power supply is through a direct current source, the cleaning system will have a sludge scraper followed by decantation. , in addition to a centrifugal pump that will suction the effluent and an automation panel to carry out the other operational controls. In the study, the process variables were determined: operational cost, current density, electrode lifetime and theoretical electrical voltage. Afterwards, the turbidity, chemical oxygen demand (COD), sedimentable solids, pH and electrical conductivity of the raw and treated effluent were evaluated. The experimental equipment developed for the treatment of effluents generated by vehicle washing did not reach sufficient values for the release of the effluent, but it proved to be capable of treating the effluent for the reuse of the process. The prototype presented an excellent result in the clarification of the treated effluent.